Sigma Factors and Stress Reactions in Micobacterias (Review) - Nailet Arráiz (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2002)
Transcription of genes in cells Prokaryotes is carried out by the holoenzyme RNA polymerase (ARNP). Purification and biochemical characterization of this enzyme has allowed to identify two components main: the so-called "core" of the ARNP and the sigma factor